2019
DOI: 10.3390/ijms20082038
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia is Associated with Sex-Specific Transcriptional and Proteomic Changes in Fetal Erythroid Cells

Abstract: Preeclampsia (PE) has been associated with placental dysfunction, resulting in fetal hypoxia, accelerated erythropoiesis, and increased erythroblast count in the umbilical cord blood (UCB). Although the detailed effects remain unknown, placental dysfunction can also cause inflammation, nutritional, and oxidative stress in the fetus that can affect erythropoiesis. Here, we compared the expression of surface adhesion molecules and the erythroid differentiation capacity of UCB hematopoietic stem/progenitor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 109 publications
3
12
0
Order By: Relevance
“…Additionally, we show that fetuses from PE pregnancies without FGR did not present any difference compared to controls. These findings were independent of fetal sex in line with previous reports on comparable free HbF levels among male and female fetuses [37,38].…”
Section: Results Of the Study In The Context Of Other Observationssupporting
confidence: 92%
“…Additionally, we show that fetuses from PE pregnancies without FGR did not present any difference compared to controls. These findings were independent of fetal sex in line with previous reports on comparable free HbF levels among male and female fetuses [37,38].…”
Section: Results Of the Study In The Context Of Other Observationssupporting
confidence: 92%
“…The following are available online at , Figure S1: Negative controls for antibodies and in situ hybridization probes, Figure S2: In situ analysis of alpha- and gamma-globin mRNAs in placenta stroma, Figure S3: Semi-quantification of the images from immunostaining analyses using ImageJ, Table S1: Detailed description of clinical characteristics of the patients for each set of experiments [ 73 ].…”
mentioning
confidence: 99%
“…There is a lack of evidence regarding a molecular basis for the association between fetal sex and PE. Our previous study showed that CD99 mRNA was upregulated in umbilical cord blood erythroid cells from male fetuses in PE pregnancies [16], and we speculated that CD99 expression, regulated by the SNP rs311103 genotype, might play a role in the pathogenesis of PE in a fetal sex-dependent fashion.…”
Section: Discussionmentioning
confidence: 93%
“…The obstetric outcomes are determined by complex interactions between the mother, the placenta and the fetus in a fetal sex-dependent fashion [15]; the exact mechanisms, however, are not known. Recent transcriptome findings by Masoumi et al gave an indication that CD99 expression is upregulated in umbilical cord blood erythroid cells in male fetuses from PE pregnancies [16].…”
Section: Introductionmentioning
confidence: 99%